The Hart-Fuller Debate on Law and Morality Within the Prism of the Legal Foundation of the Right to Privacy in its Earlier Jurisprudential Interpretations in German Case-Law - Lytvynenko, Anatoliy A. (Teisė, 2021)
The 1950s debate between the British and American legal philosophers, Lon Fuller and Herbert Hart, has been a clash between the positivist and natural theories of origination of law and jurisprudence, with the former method primarily suggesting that law and morality are not necessarily interconnected, though may coincide in some occurrences, while the latter sticks to development of law that is based upon the mores and values related to human nature, which creates the standards that society should follow in order to function properly. The former approach, as it is argued, is not actually deprived of moral factors. To examine how these debates could work on practice, I decided to choose the early developments of the general right to privacy as an example of “penumbral” rights and to review the positions of various courts within adjudicating cases in respect with the general right to privacy.
Keywords: law and morality; right to privacy; German law; Reichsgericht; medical confidentiality; history of law; data privacy